Μ‐Opioid receptors mediate the effects of chronic ethanol binge drinking on the hippocampal neurogenic niche. (6th March 2013) - Contet, Candice; Kim, Airee; Le, David; Iyengar, Siddharth K.; Kotzebue, Roxanne W.; Yuan, Clara J.; Kieffer, Brigitte L.; Mandyam, Chitra D.
Abstract Ethanol exposure and withdrawal alter the generation of new neurons in the adult hippocampus. The endogenous opioid system, particularly the μ‐opioid receptor (MOR), can modulate neural progenitors and also plays a critical role in ethanol drinking and dependence. In the present study, we sought to determine whether MOR contributes to the effects of ethanol on the dentate gyrus (DG) neurogenic niche. MOR wild‐type (WT), heterozygous (Het) and knockout (KO) littermates were subjected to voluntary ethanol drinking in repeated limited‐access two‐bottle choice (2BC) sessions. MOR deficiency did not alter progenitor proliferation, neuronal differentiation and maturation, apoptosis or microglia in ethanol‐naïve mice. When exposed to five consecutive weeks of 2BC, MOR mutant mice exhibited a gene‐dosage‐dependent reduction of ethanol consumption compared with WT mice. Introducing a week of ethanol deprivation between each week of 2BC increased ethanol consumption in all genotypes and produced equivalent intakes in WT, Het and KO mice. Under the latter paradigm, ethanol drinking decreased progenitor proliferation and neuronal differentiation in the DG of WT mice. Interestingly, WT mice exhibited a strong negative correlation between ethanol intake and proliferation, which was disrupted in Het and KO mice. Moreover, MOR deficiency blocked the effect of ethanol on neuronal differentiation. MOR deficiency also protected against the neuroimmune response to ethanol drinking. Finally, chronic binge drinking induced a paradoxical decrease in apoptosis, which was independent of MOR. Altogether, our data suggest that MOR is implicated in some of the neuroplastic changes produced by chronic ethanol exposure in the DG.